Colleges and schools-College of Agricultural Sciences and Technology-Plant Science 082
Dr. Harry Karle, Chairman of the Department of Plant Science at California State University, Fresno, presents the Department's Student Achievement Award to Dale Carlson of Lodi, a viticulture student.